Features of the Use of Modern Information Technologies in Teaching the Subject of the Solution (Texas Journal of Multidisciplinary Studies, 2022)
Effective use of modern information technologies and Internet resources in the teaching of solutions in chemistry. Convenience and advantages of using modern information technologies